2005
DOI: 10.1126/science.1105466
|View full text |Cite
|
Sign up to set email alerts
|

Slip-Rate Measurements on the Karakorum Fault May Imply Secular Variations in Fault Motion

Abstract: Beryllium-10 surface exposure dating of offset moraines on one branch of the Karakorum Fault west of the Gar basin yields a long-term (140- to 20-thousand-year) right-lateral slip rate of approximately 10.7 +/- 0.7 millimeters per year. This rate is 10 times larger than that inferred from recent InSAR analyses ( approximately 1 +/- 3 millimeters per year) that span approximately 8 years and sample all branches of the fault. The difference in slip-rate determinations suggests that large rate fluctuations may ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
151
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(163 citation statements)
references
References 20 publications
11
151
0
1
Order By: Relevance
“…This implies that only the oldest boulder ages should be used to conservatively assess moraine age and in this case the slip rate would concur with that of Brown et al (2002) and the published geodetic rates. Although Chevalier et al (2005) conceded that interpretation of a dispersed dataset is complex, and that the degree to which surface exposure ages are affected by surface reworking is 'not solidly established', they concluded that their glaciotectonic model represents the simplest and most likely interpretation.…”
Section: Quaternary and Holocene Offsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that only the oldest boulder ages should be used to conservatively assess moraine age and in this case the slip rate would concur with that of Brown et al (2002) and the published geodetic rates. Although Chevalier et al (2005) conceded that interpretation of a dispersed dataset is complex, and that the degree to which surface exposure ages are affected by surface reworking is 'not solidly established', they concluded that their glaciotectonic model represents the simplest and most likely interpretation.…”
Section: Quaternary and Holocene Offsetsmentioning
confidence: 99%
“…More recently, Chevalier et al (2005) suggested a slip rate of 10.7 AE 0.7 mm a À1 based upon 10 Be dating of quartz cobbles taken from offset glacial moraines. By deriving both a surface age and a displacement they concluded that, as the millenial slip rate is an order of magnitude greater than that determined by InSAR (Wright et al 2004), then it implies secular variation in slip.…”
Section: Quaternary and Holocene Offsetsmentioning
confidence: 99%
“…Defining the ages of landforms and sediments throughout much of the HimalayanTibetan orogen has been particularly difficult because of the Shiraiwa, 1993;Sharma and Owen, 1996;Phillips et al, 2000;Richards et al, 2000a,b;Owen et al, 2001Owen et al, , 2002aOwen et al, ,b, 2003aOwen et al, ,b,c, 2005Owen et al, , 2006aSchäfer et al, 2002;Tsukamoto et al, 2002;Yi et al, 2002;Finkel et al, 2003;Zech et al, 2003Zech et al, , 2005Barnard et al, 2004aBarnard et al, ,b, 2006aMeriaux et al, 2004;Spencer and Owen, 2004;Chevalier et al, 2005;Abramowski et al, 2006;Colgan et al, 2006;Seong et al, 2007Seong et al, , 2008a. The red dots in part (A) highlight regions where TCN surface exposure dating has been undertaken.…”
Section: Extent Of Glaciationmentioning
confidence: 99%
“…60 and 30 ka, and that glaciers advanced during the early to middle Holocene. A plethora of papers following this work emerged and they included distant regions throughout the HimalayanTibetan orogen (Owen et al, , 2002a(Owen et al, ,b, 2003a(Owen et al, ,b,c, 2005Schäfer et al, 2002;Finkel et al, 2003;Zech et al, 2003Zech et al, , 2005Barnard et al, 2004aBarnard et al, ,b, 2006aMeriaux et al, 2004;Chevalier et al, 2005;Abramowski et al, 2006;Seong et al, 2007Seong et al, , 2008a. summarised the TCN studies and suggested that the regional patterns and timing of glaciation reflect temporal and spatial variability in the South Asian monsoon and, in particular, in regional precipitation gradients.…”
Section: Timing Of Glaciationmentioning
confidence: 99%
“…However, these input parameters have been measured with high spatiotemporal accuracy only for the last few decades, an observation period much shorter than the recurrence interval of most faults (Yeats and Prentice, 1996). Given that slip rate and micro-seismic activity of a fault may not be constant through its seismic cycle (e.g., King and Bowman, 2003;Chevalier et al, 2005), the short observation period of these input parameters limits reliable evaluation of long-term seismic patterns. Hence, paleoseismic data spanning at least several seismic cycles becomes crucial to improve the outcomes of seismic hazard assessment analyses.…”
Section: Introductionmentioning
confidence: 99%